Regulação do etileno em cafeeiros cultivados sob diferentes níveis de déficit hídrico - Avelar, Rafaella de Paula (2018)
Coffee cultivation has historically been a major economic activity in Brazil, and Brazil is currently the world's largest producer and exporter of coffee. Coffee trees show flowering of the gregarious type, that is, all plants bloom at the same time in a c ertain region, however, the number of flowering events is variable, from few events like it occurs in Brazil, to many events as it occurs in Colombia. Asynchronous flowering causes difficulties related to partial harvesting, disease control, pest control, reduction in grain quality, and increases harvesting costs. Coffee flowering is divided into three stages: floral initiation or differentiation, rest or quiescence, and floral opening, or anthesis, being triggered by precipitation or irrigation after a period of water deficit. The response to rehydration has been associated with an increase in ethylene levels. This increase may be involved in the control of coffee anthesis promotion.There is evidence that this increase may be related to the transport of the ethylene precursor (ACC) from the roots to the shoot via the vascular system. However, the effect of water deficit on the regulation of ethylene and on vascular system development is poorly understood. T herefore, studies in this sense are fundamental to understand the mechanism of ethylene regulationand the development of the vascular system in plants under water deficit. The elucidation of these mechanisms may help to understand the influence of ethylene on flowering in future works. In this way ,this study tested the hypothesis that rehydration causes a great increase in the ethylene production in the shoot and that water deficit affects the development of the vascular system in leaves of coffee trees. To test this hypothesis, analyzes of gene expression and anatomy were performed. In the gene expression analyzes, the expression levels of ethylene biosynthesis and signaling genes in well-wateredand water deficit plants, as well as after plant rehydration, were analyzed. In the anatomical analyzes, cross sections were made in young leaves of well-watered and water deficit plants. The gene expression analyzes suggest that plants under water deficit show a reductionin the production of ethylene in the shoot and an increase the synthesis of ACC in the root. In addition, it is suggested that rehydration causes a reduction of the ethylene production in the leaves, followed by an increase in their synthesis. Anatomical data indicate s that leaves from plants growing under water deficit have a larger number of xylem vessels and larger phloem area.